A study on efficacy of induction training programme in Indian railways using factor analysis - Chidambaram, Vijayabanu; Ramachandran, Amudha; Thevar, Surulivel Sangeli (Business: Theory and Practice, 2013)
The induction training is very vital for all the new recruits. It helps to reduce the time and cost for the employees to adhere to the organization and facilitate the new employees to perform effectively. It helps the employees to feel with greater morale and they create oneness and cohesiveness among the members of the organization. Hence this internal motivation, the warm feeling as well as initial level of skills and knowledge imparted by the induction training helps the new recruits to glue themselves easily to their job and towards the organization. The study analyze the factors that influences the effectiveness of induction training programme and the impact of induction training programme towards middle and lower level employees using factor analysis.